2014
DOI: 10.5014/ajot.2015.691001
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the Value and Quality of Occupational Therapy in Health Service Delivery

Abstract: The authors set forth a foundation on which to build further dialogue and evidence to highlight occupational therapy’s distinctive contribution, significance, and viability as health care policies shift to focus on quality and value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Best practice guidelines and protocols promote the routine and systematic collection of outcome data as part of the process of continually improving the care and the health outcomes of clients and to support evidence-based practice (Boswell, Kraus, Miller & Lambert, 2015;Hubbard et al, 2012). The importance of collecting this data is increasingly apparent as health care funding allocation is being tied to outcomes data (Leland, Crum, Phipps, Roberts & Gage, 2014). Measures like Aus-TOMs-OT provide occupational therapists with an opportunity to regularly collect outcomes data efficiently, and with few resource implications, in everyday practice.…”
Section: Introductionmentioning
confidence: 99%
“…Best practice guidelines and protocols promote the routine and systematic collection of outcome data as part of the process of continually improving the care and the health outcomes of clients and to support evidence-based practice (Boswell, Kraus, Miller & Lambert, 2015;Hubbard et al, 2012). The importance of collecting this data is increasingly apparent as health care funding allocation is being tied to outcomes data (Leland, Crum, Phipps, Roberts & Gage, 2014). Measures like Aus-TOMs-OT provide occupational therapists with an opportunity to regularly collect outcomes data efficiently, and with few resource implications, in everyday practice.…”
Section: Introductionmentioning
confidence: 99%
“…Employers indicated that they desired employees who could articulate the role and value of OT. Leland, Crum, Phipps, Roberts, and Gage (2014) offered that this is imperative in the context of health care reform. Applying these policy-driven shifts to the concept of professionalism validate Hordichuk et al's (2015) description of the changing nature of professionalism and reinforce Bossers et al's (1999) description of knowledge, behaviors, and accountability.…”
Section: Category 3: Respect For the Profession Department And Companymentioning
confidence: 99%
“…EHRs have become the dominant technology in health care (Borycki, Joe, Armstrong, Bellwood, & Campbell, 2011). To prepare students to use health information technology, academic programs should provide EHR training in their curricula (Leland, Crum, Phipps, Roberts, & Gage, 2015). At this time, there are no publications describing if and how EHR instruction is implemented in entry-level OT and OTA programs.…”
Section: The Accreditation Council For Occupationalmentioning
confidence: 99%
“…Another respondent stated "the most important thing is that students learn good that is available for authorized users to conduct research (Menachemi & Collum, 2011). OT researchers who use the EHR as an emerging data source can build on existing evidence to justify their decisions (Leland et al, 2015). For example, standardized assessments embedded in EHR software produces objective data to validate OT outcomes and inform decisions about the therapy process (Morley, 2014).…”
Section: Faculty Perspectives Of Ehrs In Academiamentioning
confidence: 99%